Development of actions on optimization of chemical composition of carburized steel grade 16MnCrS5 to eliminate the causes of the growth of large austenite grains - I. A. Kovaleva; I. A. Ovchinnikova; S. V. Stefanovitch (Литьë и металлургия, 2019)
The problem of friction, wear of machine parts and cutting tools, the need to increase the life of machines makes the task of creating new high-performance, energy-saving technologies of hardening one of the main in engineering. In mechanical engineering, the problem of improving the physical, mechanical and operational properties in thin surface layers (~10 microns) of such parts as shafts, gears, measuring tools, drills, cylinders of internal combustion engines, etc. is important. Currently, these tasks are often solved by applying reinforcing coatings. Cementation is economical. The technology of cemented steels smelting, which is currently used by metallurgical plants, does not ensure stable production of fine-grained structure in products. At the same time, the capacity of machines and units are growing, and to obtain parts that can withstand higher loads while maintaining their overall dimensions, new steel grades are needed. The complexity of the configuration of gears with a thin tooth and a massive sleeve, and the need for minimal warping make heat treatment as difficult and responsible as a complex tool, such as shaped cutters. Therefore, for the manufacture of gears you want to assign steel with small hereditary grain size. In this article we will focus on the development and production of cemented steel in the conditions of OJSC «BSW – Management Company of Holding «BMC», in particular, the steel brand 16MnCrS5 commissioned by the European manufacturer of gearboxes and motors. To determine the grain size of the metal must be subjected to special types of processing for the manifestation of certain characteristics. These results allow us to draw conclusions about the need to adjust the chemical composition of steel grade 16MnCrS5 by introducing a system of modifying elements, which will reduce the tendency of steel to overheating, therefore, reduce the size of austenitic grains. On the basis of the revealed regularities on the influence of carbide-forming elements, a further system of steel modification is determined, which includes a complex of elements V, Nb, Ti.